Annular Pancreas in Adults: A Report of Two Cases and Review of Literature - Wani, Ajaz Ahmed; Maqsood, Shadab; Lala, Parvez; Wani, Sheema (JOP. Journal of the Pancreas, 2013)
Context Annular pancreas is one of the rare congenital anomalies that can manifest itself in adulthood also. No specific guidelines and protocols exist about management of such cases. We hereby discuss our experience with two such cases along with a brief review of literature about the subject. Case reports The first patient was a male aged 27 years and presented with features of duodenal obstruction. He underwent duodenoduodenostomy . The second patient, a male aged 32 years, also presented with features of gastric outlet obstruction. He underwent Billroth type 2 reconstruction. Both patients had an uneventful recovery. Conclusion Annular pancreas in adults is a rare clinical scenario. Advancements in imaging modalities have brought to forefront an even larger number of such cases. In adults it is diagnosed mainly because of the complications that arise thereof. Gastroduodenal tuberculosis can be an important differential diagnosis in endemic areas. Treatment and operative protocols have to be individualized. Image: Complete ring of pancreatic tissue encircling the second part of duodenum.